Acute pancreatitis: international classification and nomenclature. Issue 2 (February 2016) - Bollen, T.L.
Abstract : The incidence of acute pancreatitis (AP) is increasing and it is associated with a major healthcare concern. New insights in the pathophysiology, better imaging techniques, and novel treatment options for complicated AP prompted the update of the 1992 Atlanta Classification. Updated nomenclature for pancreatic collections based on imaging criteria is proposed. Adoption of the newly Revised Classification of Acute Pancreatitis 2012 by radiologists should help standardise reports and facilitate accurate conveyance of relevant findings to referring physicians involved in the care of patients with AP. This review will clarify the nomenclature of pancreatic collections in the setting of AP.